Joint MDB Report to the G8 on the Implementation of the Clean Energy Investment Framework and Their Climate Change Agenda Going Forward - African Development Bank (World Bank, Washington, DC, 2017)
The 2005 Gleneagles G8 summit in July 2005 stimulated a concerted effort of the Multilateral Development Banks (MDBs) to broaden and accelerate programs on access to energy and climate change mitigation and adaptation through the Clean Energy Investment Framework (CEIF). At the Gleneagles summit, it was agreed that a report on the implementation of the CEIF would be prepared for the 2008 G8 (Group of Eight: Canada, France, Germany, Italy, Japan, Russia, the United Kingdom, and the United States) summit hosted by Japan. This joint report of the MDBs to the G8 summit in Hokkaido is intended to provide information on the outcomes and lessons learned under the CEIF, describe the collective MDB objectives for addressing the energy access and climate change challenges, and outline how the MDBs plan to build on the CEIF experience to date to more fully achieve these objectives. The report builds upon the 'the MDBs and the climate change agenda' report that was presented at the December 2007 Bali climate change conference. This report describes actions taken by each MDB to develop climate change strategies and programs of actions tailored to their particular client needs, based on resources and funding mechanisms currently available. Under the CEIF, the MDBs have strengthened collaboration on analytical work and programming and committed to expand this collaboration to optimize the impact of their collective actions. In addition to reporting on the status of the CEIF, this report outlines the collective ambition of the MDBs with respect to assisting the developing countries in meeting the climate change challenge, summarizes their evolving strategies designed to meet these objectives and the mechanisms through which they intend to achieve the necessary collaboration to optimize the collective impact of their climate change interventions.